FROM HOMO FABER TO HOMO ALGORITHMICUS: THE IMAGO DEI IN TRANSFORMATION - Marcos Borges Paes, Tadeu; Souza Borges, Walter (Revista Gênero e Interdisciplinaridade, 2026)
The transition from Homo faber, traditionally defined by the capacity to shape and transform the world through labor, to what can be described as Homo algorithmicus represents a profound shift in how human beings create, decide, and relate to reality. The growing mediation of Artificial Intelligence in cognitive, creative, and decision-making processes raises central questions for theological anthropology, particularly regarding the understanding of the Imago Dei—the image of God in the human person. This article examines how Artificial Intelligence reconfigures human agency, creativity, and moral responsibility, investigating whether these transformations constitute a threat to, a dilution of, or a renewed expression of the Imago Dei. Through a qualitative, theoretical-conceptual, and interdisciplinary approach, the study brings into dialogue contemporary ethics of Artificial Intelligence and the theological tradition of creation. It argues that the Imago Dei cannot be reduced to productive capacity or cognitive superiority, but is fundamentally expressed in the relational, ethical, and responsible dimensions of human action. The findings indicate that Homo algorithmicus does not replace Homo faber, but redefines it by expanding human creative power while simultaneously intensifying moral responsibility. Far from being eliminated by algorithmic mediation, the Imago Dei is placed under unprecedented historical tension, demanding a critical reinterpretation that preserves human dignity as a normative criterion in increasingly algorithm-driven sociotechnical environments.